GSM Based Smart Distribution System - Muhammad Ilyas Afridi; Shah Faisal; Hikman Ud Din Bangash; Qazi Waqar Ali; Arsalan Arif (Institute of Advanced Engineering and Science, 2012)
Nontechnical losses (NTL) during transmission of electrical energy are a main problem in developing countries. It is so complicated for the utility companies to detect and fight the people responsible for the theft. Electricity theft forms a main chunk of non technical losses (NTL). These losses affect the quality of supply, increase load on the generating station, and affect tariff forced on actual consumers. This paper shows some common methods used by consumers for electricity theft and also proposes an architectural distribution system for theft detection using GSM based smart energy meter. The Inspiration of this work is to detect illegal consumers, preserve and successfully utilize energy. As well as smart meters are proposed to provide automatic readings/data of dissimilar parameters related to instantaneous power consumption via GSM. It will reduce the laborious task and financial expenditure by adopting the automatic meter reading instead of the manual meter reading process and bill data entry process.DOI:http://dx.doi.org/10.11591/ijece.v2i5.1558